Improving Competition Events Interest with Odoo ERP: Efficient Reimbursement and Achievement Management for Educational Institutions - Suri, Fhina Atika; Hediyanto, Umar Yunan Kurnia Septo; Firdaus, Taufiq Maulana (STKIP PGRI Tulungagung, 2025)
This research designs an Enterprise Resource Planning (ERP) system, using Odoo through the Quickstart method to overcoming problems in managing and storing achievement data and competition reimbursement submission in educational institutions. This system is designed to facilitate database management, record competition activities from the initial stage to the announcement, and monitor competition reimbursement submission through a dashboard. System testing using the blackbox testing method has been carried out successfully, while user acceptance testing shows an acceptance rate of 88%, which is categorized as very acceptable. These results are in line with the initial objective of the research, which is to design a system to support improving of student interest in contributing to competitions.